Jaringan Sosial (Networks) dalam Pengembangan Sistem dan Usaha Agribisnis: Perspektif Teori dan Dinamika Studi Kapital Sosial - Ketut Gede Mudiarta (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2009)
EnglishThe limited possession of resources such as physical capital especially land, finance, and technology need social resources empowerment as potential local resources followed by equality and inclusiveness in implementing of development programs. This paper tries to elaborate sociological theory in the dynamics of social capital study especially social networks linked to the social reality on empirical level. In line with the theories of new institutionalism, social networks, diffusion of innovation, and social mobilit, on the empirical level it shows that agribusiness development is not supported by synchronization of policy environment in macro level, informal rules at meso level, and individual needs in micro level and availability of informal rules at meso and micro levels in the community. The failure of agribusiness development is also believed to be affected by unequal social-resources and also by less concern on the effect of economic benefit on social network, i.e. without considering the following aspects, e.g. (i) Norm and density network; (ii) The Strength of Weak Ties; (iii) The Importance of